Clinical Evaluation of NESOSPRAY HE-C, a Nasal Spray, for Rhinopharyngitis and Rhinosinusitis: A Randomized, Double-Blind, Placebo-Controlled Trial - Fatima-Zahra El Barche; Manon D’almeida; Séverine Dameron; Rémi Shrivastava (Medicina)
Background and Objectives: The common cold (acute rhinopharyngitis) and acute rhinosinusitis are highly prevalent conditions that significantly impact quality of life, often leading to nasal congestion, inflammation, and discomfort. Given the growing demand for non-pharmacological treatment options, particularly for vulnerable populations such as children and pregnant women, alternative therapies are increasingly being explored. NESOSPRAY HE-C, a nasal spray formulated with a glycerol-based filmogenic solution, acts by forming a protective osmotic film on the nasal mucosa. This mechanism facilitates mechanical cleansing, enhances decongestion, and reduces inflammation while preserving mucosal integrity. Its purely topical and mechanical mode of action provides a non-systemic alternative for symptom management. Materials and Methods: This randomized, double-blind, parallel-group clinical trial evaluated the efficacy and safety of NESOSPRAY HE-C (n = 29) compared to a placebo nasal spray (n = 26) in patients aged ≥ 3 years diagnosed with the common cold or acute rhinosinusitis. Participants had a baseline Rhinosinusitis Symptom Severity Score (RSSS) of ≥25/50. Treatment consisted of administering 2–3 sprays per nostril, four times daily, every 4 to 6 h, for up to 8 days or until symptom resolution. The primary outcomes included changes in total RSSS, Wisconsin Upper Respiratory Symptom Survey (WURSS) score, and individual symptom scores (rhinorrhea, nasal congestion, cough, poor sleep, facial pain, and fever). Safety assessments included adverse event monitoring and treatment tolerability, with subgroup analyses performed for children and pregnant women. Results: Baseline demographics were comparable between the treatment groups. NESOSPRAY HE-C demonstrated a significantly greater reduction in total RSSS from Day 3 onward (p = 0.0008), with sustained superiority through Day 8 (p < 0.0001). Significant improvements in rhinorrhea and nasal congestion were observed within 2 h of administration (p = 0.0089), while reductions in cough (p = 0.0052), poor sleep (p = 0.0005), and facial pain (p = 0.0111) emerged by Day 3. Fever reduction was most pronounced on Days 6 (p = 0.0001) and 8 (p = 0.0312), indicating a delayed but significant effect. In terms of the WURSS score, NESOSPRAY HE-C showed a significant improvement from Day 1, with a greater reduction in symptom severity compared to placebo. This trend of greater improvement continued through Day 8. The treatment was well tolerated, with no reports of serious adverse events or allergic reactions. Efficacy was consistent across all subgroups, including children, pregnant women, and adults. Conclusions: NESOSPRAY HE-C provides rapid and sustained symptom relief for the common cold and acute rhinosinusitis, serving as a safe and effective non-pharmacological alternative to conventional treatments. By leveraging its osmotic action and barrier-forming properties, it facilitates mechanical cleansing, enhances decongestion, and reduces inflammation while preserving mucosal integrity. Additionally, by forming a protective film on the nasal mucosa, it protects against future irritations, further supporting its role as a valuable therapeutic option, particularly for individuals seeking non-systemic symptom management.